Employee career adaptability and perceived cohesion on innovative behavior: Mediating and moderating effects - Jiang, Xiaoyu; Wang, Jia-Fure (Edelweiss Applied Science and Technology, 2025)
This study examines how employee career adaptability and perceived cohesion influence innovative behavior, with work engagement as a mediator and leadership power distance and individual learning ability as moderators. Drawing on career construction theory and the job demands-resources model, we investigate the psychological mechanisms and boundary conditions that shape innovation in R&D contexts. Using a cross-sectional design, we collected data from 533 R&D employees in large Chinese manufacturing firms and analyzed it through structural equation modeling and moderated regression analysis. The results reveal that both career adaptability and perceived cohesion significantly enhance innovative behavior, with work engagement partially mediating these relationships (indirect effects). Leadership power distance weakens the positive effects of career adaptability on innovation and work engagement, while individual learning ability strengthens these relationships. Notably, power distance did not moderate the cohesion-engagement link, suggesting team bonds may buffer against hierarchical constraints. These findings highlight the dual pathways—direct and through engagement—by which adaptability and cohesion foster innovation, while emphasizing the contextual roles of leadership structures and learning capability. For organizations, the study underscores the need to reduce hierarchical barriers, cultivate adaptive career mindsets, and promote continuous learning to maximize innovation potential. The research contributes to career construction and JD-R theories by integrating personal, social, and organizational factors in innovation processes.